1997
DOI: 10.1203/00006450-199710000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemic Events in Spontaneously Breathing Premature Infants: Etiologic Basis

Abstract: Studies of severe hypoxemic events, defined as an arterial oxygen saturation < 80% greater than 4 s in spontaneously breathing infants, have been limited. The purpose of our study was to examine the distribution of respiratory events that lead to a fall in oximetrically measured oxygen saturation by using breathing patterns, heart rate, and validated pulse oximetry analysis. A total of 161 hypoxemic events were detected in 18 of 30 premature infants studied. Using an inductive plethysmographic based monitor, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 26 publications
1
24
0
1
Order By: Relevance
“…The proportion of apneic events with blood-O 2 - desaturation increases with lower baseline blood O 2 -saturation measured just before the apneic event. This confirms previous data (25). As a result, hypoventilation and low basal blood O 2 -saturation values are associated with low O 2 reserves and may increase the likelihood of blood O 2 -desaturation-even during short apneic events.…”
Section: Discussionsupporting
confidence: 80%
“…The proportion of apneic events with blood-O 2 - desaturation increases with lower baseline blood O 2 -saturation measured just before the apneic event. This confirms previous data (25). As a result, hypoventilation and low basal blood O 2 -saturation values are associated with low O 2 reserves and may increase the likelihood of blood O 2 -desaturation-even during short apneic events.…”
Section: Discussionsupporting
confidence: 80%
“…Frequent episodes of oxygen desaturation have been reported to occur in asymptomatic premature infants, 5 and investigations have found that 75% of hypoxemic events in spontaneously breathing prematures would have gone undetected using our current practice of respiratory monitoring based on impedance pneumography and electrocardiography. 6 Our data suggest that infants at risk for apnea may experience minor perturbations in heart rate but large perturbations in oxygen saturation. Because the degree of oxygen desaturation may not be predicted by heart rate changes, it appears that home monitoring devices should include oxygen saturation detection.…”
Section: Discussionmentioning
confidence: 95%
“…The mechanism by which supplemental oxygen may prevent desaturation events or decrease their severity is unknown; however, it is hypothesized that supplemental oxygen increases the end-expiratory lung volume thereby improving ventilation/perfusion matching [28]. More research is needed to examine the effect of supplemental oxygen on early preterm infant feeding skills and to determine which infants may benefit most from the use of supplemental oxygen during feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Poets et al [22] found that lower baseline SpO 2 was correlated with an increase in transient desaturations. Adams et al [28] found that preterm infants with lower baseline SpO 2 were more vulnerable to hypoxemic events with even brief interruptions in their breathing. In infants with chronic lung disease, McEvoy et al [29] reported less number and duration of desaturation events when infants' SpO 2 was maintained at a level of 94-96% rather than 87-91%.…”
Section: Discussionmentioning
confidence: 99%